Ekonomi Islam dan Sustainable Development Goals (SDGs) - Rahmatia; Trimulato (Al-Buhuts, 2020)
The development of Islamic economics in Indonesia continues to grow and is much in demand by the wider community. Islamic economics is expected to contribute to the economy in this country, including the realization of Sustainable Development Goals (SDGs). Islamic economics has many financial instruments including Sharia Banking, Sharia industries financial of non-bank (IKNB Syariah) and social fund raising institutions. This financial institution continues to grow and develop, the sharia banking market share reaches 5.8 percent, the IKNB Syariah products are increasing, and the collection of social funds through the Funding of Zakat institution makes social funds well organized both in their collection and distribution. People can access all instruments of Islamic economic institutions to help their economy. This research is a literature study and uses uses qualitative descriptive analysis techniques. This study describes the growth of Islamic economic institutions and the economic role of Islam for the realization of the SDGs. The results of this study show that sharia banking continue to experience asset growth in the period of 2017. Sharia banking has assets reached 477,327,000,000,000 or grew by 12.53%. The growth of Sharia IKNB increased in 2018 by 35 institutions or grew by 64.81%. In the collection of funds there was a growth of 17.48 for infaq and shadaqah, while other social funds grew by 120.86%. Islamic economics and all its instruments, including Islamic economic institutions consisting of sharia banking, sharia IKNB and social fund collection institutions have the same purpose as the SGDs concept that the government wants to achieve. So that the existence of Islamic economic institutions has an important role to reach the SDGs especially to achieve economic prosperity and equality of better livelihoods and poverty alleviation.